THE EFFECT OF USING CLOZE PASSAGE TECHNIQUE TOWARD STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT THE EIGHTH GRADE OF SMPN 8 KOTA SERANG - Sutrisno Sadji Evenddy; Fenturisa Kusfitriyatna; Dhafid Wahyu Utomo (Journal of English Language Learning, 2021)
The aim of this research was to find out whether the Cloze Passage Technique has effect on students’ reading comprehension in narrative text. This research was conducted at the eighth grade of SMPN 8 Kota Serang in academic year 2019/2020 during the COVID-19 pandemic. This research used quantitative method and true experimental design. The populations of this research were all classes in class VIII. The sample of this research were class VIII B which consisted 0f 20 students as the experimental class and class VIII F which consisted of 20 students as the control class. The experimental class was taught by using Cloze Passage Technique and control class without using Cloze Passage Technique. The research instrument was a test which consisted pre-test and post-test. The pre-test was given to students before treatment and the post-test was given to students after treatment. After collected and calculated the data, it was found that there was any effect of using Cloze Passage Technique. This was indicated by the value of tcount was higher than ttable (5,131 ≥ 2,024) at the level of significance of α 0,05 and degree of freedom is 38. It means that the alternative hypothesis (Ha) was accepted. For those findings, this research showed that there is any effect of using Cloze Passage Technique on students’ reading comprehension in narrative text.